SUBNATIONAL MARITIME DIPLOMACY IN ADVANCING SDG 14: A CASE STUDY OF SUSTAINABLE FISHERIES GOVERNANCE IN BERAKIT VILLAGE, RIAU ISLANDS - Anastasia Wiwik Swastiwi; Eki Darmawan; Uly Sophia; Rizqi Apriani Putri; Nur Aslamaturrahmah Dwi Putri (SOSIOEDUKASI, 2026)
This study examines how subnational maritime diplomacy contributes to the advancement of Sustainable Development Goal (SDG) 14 in Indonesia’s maritime border context. While SDG 14 (Life Below Water) is commonly operationalized through national-level marine policies, limited scholarship explores the role of local governments as diplomatic and governance actors in achieving sustainable fisheries outcomes. Using a qualitative case study approach, this research investigates sustainable fisheries governance practices in Berakit Village, Riau Islands Province, a strategically located coastal border area facing transboundary fisheries pressures. Data were collected through in-depth interviews with local officials, fisheries officers, community leaders, fishermen groups, and supporting institutions, complemented by policy document analysis and field observations. The findings demonstrate that subnational maritime diplomacy functions as a governance interface linking local community-based practices with national sustainability commitments. Key contributions include strengthening spatial regulation under the Coastal and Small Islands Zoning Plan (RZWP3K), promoting selective fishing gear, enhancing community-based monitoring to deter Illegal, Unreported and Unregulated (IUU) fishing, and fostering collaborative networks with national and cross-border actors.These initiatives align with SDG 14 targets, particularly 14.2 (sustainable management of marine ecosystems), 14.4 (ending overfishing), and 14.b (access for small-scale fishers). The study argues that subnational maritime diplomacy should be conceptualized not merely as external engagement, but as an adaptive governance mechanism that enhances regulatory coherence, ecological compliance, and local empowerment in decentralized maritime systems. This research contributes to expanding the analytical linkage between paradiplomacy and sustainable development governance in archipelagic border regions.